Hubungan Pola Asuh Orang Tua permisif dengan perilaku Bullying pada Anak di SD Negeri Jetis 1 Yogyakarta - Dian Fertiana Devi; Istiqomah; Sriyati (Sahabat Publikasi Kuu, 2024)
Background: The problem of bullying in Indonesia continues to increase every year, with 226 cases recorded in 2022. Bullying is a crime committed by a stronger person against a weaker person. The impact of bullying on victims, such as trauma, fear, seeking escape, declining academic achievement. The impact on the perpetrators, namely when adults can become criminals. Objective: To determine the relationship between permissive parenting patterns and bullying behaviour in children at SD Negeri (state elementary school) Jetis 1 Yogyakarta. Method: Quantitative research type with correlative design and cross-sectional time approach were performed in this study. The number of respondents was 96 children taken using total sample technique. The instruments used were permissive parenting questionnaire and bullying behaviour questionnaire that had been declared valid and reliable. The data were analysed using Spearman Rank test. Results: The results of the study showed that permissive parenting patterns were mostly in the moderate category of 66 children (68.8%) and bullying behaviour was mostly in the moderate category of 50 children (52.1%). The results of the Spearman Rank statistical test analysis showed that there was a relationship between permissive parenting patterns and bullying behaviour in children at SD Negeri Jetis 1, Yogyakarta with a p value of 0.001 (p <0.05) and a correlation coefficient value of -0.337. Conclusion and suggestion: There is a relationship between permissive parenting patterns and bullying behaviour in children at SD Negeri Jetis 1 Yogyakarta. The relationship is weak, namely -0.337 (0.20-0.399). The direction of the negative correlation means that the higher the permissive parenting pattern, the lower the bullying behaviour, and vice versa, the lower the permissive parenting pattern, the higher the bullying behaviour. Parents should provide a more democratic parenting pattern so that children avoid bullying behaviour.